Respuesta :

The translations are reflection across the x-axis, moved 3 units right, moved 5 units down

Step-by-step explanation:

[tex]f(x) = -(x-3)^{2} - 5[/tex]

If we reflect a function across the x- axis then y = f(x) becomes y = -f(x)

So it becomes [tex]f(x) = -x^{2}[/tex]

In the given function, there is a horizontal shift, moved 3 units right, then

it becomes, [tex]f(x) = -(x-3)^{2}[/tex]

In this given function, there is a vertical downward shift of 5 units , so it becomes, that is moved 5 units down, then the function becomes,

[tex]f(x) = -(x-3)^{2} - 5[/tex]